Step-by-step explanation
In a linear relationship, the y-values have equal differences. and
In an exponential relationship, the y-values have equal ratios.
so
Step 1
find the common difference ( if there is )
![\begin{gathered} \text{difference}1=\text{ 6-3=3} \\ \text{difference}2=12-6=6 \\ \text{difference3=}24-12=12 \\ \text{difference}4=48-24=24 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jwhaqo2ebeslgkwcvoszweqf8lxm63acrl.png)
we can see the diffrence is not the same, so
it is not liear
Step 2
check the common ratio
![\begin{gathered} \text{ratio }_1=(6)/(3)=2 \\ \text{ratio }_2=(12)/(6)=2 \\ \text{ratio }_3=(24)/(12)=2 \\ \text{ratio }_4=(48)/(24)=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8bh9kuk6dxno14krm2virzcgjfqidh6vhy.png)
so, the ratio is common,
therefore, the answer is
Exponential